1.原式=-x^3*x^10+x^8*x^6
=-x^13+x^14
=x^14-x^13
2.原式=x^3m*x^3m-2*x^6m
=x^6m-2x^6m
=-x^6m
3.原式=9a^2b^4+4a^2b^4
=13a^2b^4
4.原式=a^3n*b^9*a^2*b^2(2n-7)-a^(2n+2)a^nb^2n
=a^(3n+2)*b^(2n+2)-a^(3n+2)b^2n
5.原式=3x^3y^3*(4/9)*x^4y^2-(1/27)*x^6y^3*9xy^2
=(4/3)*x^7y^5-(1/27)*x^7y^5
=(35/27)*x^7*y^5
=(35/27)*(-1)^7*2^5
=-1120/27
6.原式=(-4/3)*x^2y^2*(-3/4)x^2+(-4/3)*x^2y^2*xy-(-4/3)*x^2y^2*(2/5)y^2)
=x^4y^2-(4/3)x^3y^3+(8/15)x^2y^4
7.原式=(1/2)*x^3*(-6x) -(1/2)*2x^2*(-6x) +(1/2)*(2/3)*(-6x)
=-3x^4+6x^3-2x
8.原式=4x^4y^28-4x^2y^30+4x^2y^4